1998
DOI: 10.3758/bf03199211
|View full text |Cite
|
Sign up to set email alerts
|

The organization and temporal properties of appetitive behavior in rats

Abstract: In the presence and absence of an external interfood clock stimulus (a sequence of flashing lights), rats showed a multimodal behavior pattern during successive quarters of interfood intervals (IF1) ranging from 12 to 192 sec. Responses near the feeder peaked before and just after food presentations, whereas locomotion remote from the feeder peaked toward the middle of the IF1. The temporal patterns of nosing in the feeder and remote locomotion were scalar (the time at which a response peaked in the IF1 was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 35 publications
8
30
0
1
Order By: Relevance
“…In autoshaping when CS’s become long birds will increase general activity rather than peck at a CS. Similar changes in the topography of CR’s have been described in other species (Akins, Domjan et al 1994; Silva and Timberlake 1997; Silva and Timberlake 1998; Silva and Timberlake 2005). Thus the impact of changing the C/T ratio is on the likelihood of a particular CR topography.…”
Section: 3 Time and The Emergence Of Anticipatory Conditioned Resposupporting
confidence: 83%
“…In autoshaping when CS’s become long birds will increase general activity rather than peck at a CS. Similar changes in the topography of CR’s have been described in other species (Akins, Domjan et al 1994; Silva and Timberlake 1997; Silva and Timberlake 1998; Silva and Timberlake 2005). Thus the impact of changing the C/T ratio is on the likelihood of a particular CR topography.…”
Section: 3 Time and The Emergence Of Anticipatory Conditioned Resposupporting
confidence: 83%
“…We observed that, whereas training with longer CSs that had longer and variable temporal intervals between CS and US reward presentations (interstimulus interval or ISI) generated greater PIT and little CRf, training with shorter CSs that had short and constant ISIs generated more robust CRf, and little PIT. This double dissociation is consistent with previous suggestions that CS-US temporal and/or predictive relations can markedly alter the nature or content of conditioning as well as its amount (e.g., Holland 1980;Silva and Timberlake 1998).…”
supporting
confidence: 80%
“…Thus, the probability of a specific response cannot be unambiguously taken as an index of the strength of learning, as different responses may be predominantly expressed to different duration CSs. Similar observations have been made about the impact of temporal variables on the form of CR's in fear conditioning [19], eyeblink conditioning [20], sexual conditioning [21], and other appetitive conditioning paradigms [22,23]. Thus, one should not conclude that changing contiguity of the CS and US necessarily changes the underlying learning.…”
Section: Time Affects Acquisition Speed and Asymptotementioning
confidence: 60%